Le pouvoir technologique et nucléaire - Stoffaes, Christian (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
Contemporary developments are characterized at the same time by a series of economic changes and by a crisis in, international political leadership. The extent to which the density of economic relations has increased is such that a world economy is now a reality. The growing internationalization of the processes of trade and production and the internationalization of business strategies have resulted in a concentration and an oligopolization of the world economy. In the majority of the key development sectors, about ten firms at the most share the market, inducing by that very fact, an increase in specialization and, therefore, the search for a new international division, of work. The age of low-cost energy and raw materials that ensured a marked advantage to the industrialization nations seems at an end. The arrival on world markets of Third-world countries in the process of industrialization constitutes a new challenge. International competition is situated squarely in the economic field and the new international hierarchy is being established in accordance with the capacity of each participant to adapt to these new givens.